2022 Global hunger index: Food systems transformation and local governance - von Grebmer, Klaus; Bernstein, Jill; Wiemers, Miriam; Reiner, Laura; Bachmeier, Marilena; Hanano, Asja; Towey, Olive; Chéilleachair, Réiseal Ní; Foley, Connell; Gitter, Seth; Larocque, Grace; Fritschel, Heidi; et al. (Welthungerhilfe, 2022)
As the 2022 Global Hunger Index (GHI) shows, the global hunger situation is undeniably grim. The overlapping crises facing the world are exposing the weaknesses of food systems, from global to local, and highlighting the vulnerability of populations around the world to hunger. Global Progress against Hunger Is at a Near Standstill. Global progress against hunger has largely stagnated in recent years. The 2022 GHI score for the world is considered moderate, but at 18.2, it shows only a slight decline from the 2014 score of 19.1. Indeed, one indicator used in the GHI, the prevalence of undernourishment, shows that the share of people who lack regular access to sufficient calories is increasing. As many as 828 million people were under nourished in 2021, representing a reversal of more than a decade of progress against hunger. Without a major shift, neither the world as a whole nor approximately 46 countries are projected to achieve even low hunger as measured by the GHI by 2030. A Barrage of Crises Is Undermining the Fight against Hunger. The situation is likely to worsen in the face of the current barrage of overlapping global crises—conflict, climate change, and the economic fallout of the COVID-19 pandemic—all of which are powerful drivers of hunger. The war in Ukraine has further increased global food, fuel, and fertilizer prices and has the potential to significantly worsen hunger in 2023 and beyond. These crises come on top of underlying factors such as poverty, inequality, inadequate governance, poor infrastructure, and low agricultural productivity that contribute to chronic hunger and vulnerability. Globally and in many countries and regions, current food systems are inadequate to the task of addressing these challenges and ending hunger.